2018
DOI: 10.4067/s0717-95022018000300877
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Body Composition Variations in Adolescent Soccer Players

Abstract: The aim of this study was to examine seasonal variations in body composition in adolescent soccer players. A total of 64 young male soccer players (aged 14-18 years) were recruited for this research. Body composition was assessed using the Bioelectric impedance analysis. The variables were body mass, body fat, muscle mass, fat free mass, total body water, BMI, body fat %, basic metabolic rate. Body mass did not change across the three measurement occasions. Body fat mass and body fat % significantly changed be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…For sports disciplines such as European football, the morphological structure that affects sports performance is already known [9]. There are differences in body composition between periods of the season (higher values of adipose tissue in the transition period vs. the competition period) [10] as well as differences in anthropometric values between positions of game [11]. A study conducted with young male players reported that goalkeepers have statistically significantly higher body height and humerus width compared to players who play in other team positions and more weight compared to players who play in the middle and forward positions.…”
Section: Introductionmentioning
confidence: 99%
“…For sports disciplines such as European football, the morphological structure that affects sports performance is already known [9]. There are differences in body composition between periods of the season (higher values of adipose tissue in the transition period vs. the competition period) [10] as well as differences in anthropometric values between positions of game [11]. A study conducted with young male players reported that goalkeepers have statistically significantly higher body height and humerus width compared to players who play in other team positions and more weight compared to players who play in the middle and forward positions.…”
Section: Introductionmentioning
confidence: 99%
“…Duri- ng the season, adolescent soccer players have 5-6 training sessions per week and a competitive match, which is more than in our program during the transition period. During the competitive part of the season, the total caloric consumption is much higher and due to the caloric surplus, in order to satisfy the increased energy demand of the athletes, it is normal for some parameters of body composition to change during the period of decline in sports form [31].…”
Section: Discussionmentioning
confidence: 99%
“…Morphological characteristics of topclass soccer and basketball players appear to be of great interest for some authors (Saether, 2017;Madic et al 2018;Gjonbalaj et al, 2018;Pojskic et al, 2014;Gajardo-Burgos et al, 2018) with the interest of fi nding the best morphology somatotype for particular sports, competition levels and player positions as well. Comparison of anthropometrics should support coaches with better understanding of specifi c demands of certain sport, where particular morphology profi le of athlete, combined with motor and functional abilities, should express its full potential (Gusic et al, 2017).…”
Section: Discussionmentioning
confidence: 99%